Ferroelectrics dispersed Li2SO4 composite solid electrolyte - Singh, K.; Bhoga, S.S. (University of Peradeniya. Peradeniya, 1995)
The ferolectric dispersed lithium sulphate composites have been invested using complex impedance analysis. The appearance of two semicircles in the Cole-Cole plots is discussed in the light of brick wall model. The observed breakover in the Arrhenius plots within the monoclinic region is considered to be due to changover mechanism from bulk conduction (within grain) to surface percolation conduction. A considerable enhancement in conductivity due to KNbO3 is observed to be due to its ferroelectric property. The surface charge transfer mechanism at the interface is illustrated to understand the formation of a space charge layer and so the microscopic conduction process.
Keywords: Chemistry; Lithium sulphate; Ionic conductivity; Ceramics; Composites; Impedance analysis; Ferroelectrics; Electrolytes